Communication Network Structures and Content of Men with Prostate Cancer: Models for Explaining Health-Related Quality of Life. Issue 5 (4th May 2018) - Brown, Dot; Miller, Steven; Oetzel, John
ABSTRACT: Communication networks contribute to health-related quality of life (HRQOL) for men living with prostate cancer. However, the mechanisms for understanding how communication networks shape HRQOL are not well understood. The purpose of this study was to test three models explaining the communication networks and related communication variables for HRQOL. A total of 214 men with prostate cancer in New Zealand completed a survey questionnaire describing aspects of their networks including opportunities for connection, social support/undermining, status disclosure, communication efficacy, and HRQOL. The findings support a mediating model of communication networks where social undermining has a direct and negative impact on HRQOL, and an indirect effect mediated through communication efficacy, which has a direct and positive impact on HRQOL. Contrary to previous studies, social support and disclosure did not significantly impact HRQOL in this sample. The benefits of developing communication efficacy and reducing social undermining for enhancing long-term psychosocial health in this cohort of men are two key findings.